The Impact of the Thinking Style on Teaching Methods and Academic Achievement - Sahatcija, Roland; Ora, Ariel; Ferhataj, Anxhela (European Scientific Journal, ESJ, 2017)
Thinking style is an area of interest for researchers. It influences the decision-making of individuals in every aspect of their life. Does thinking style influence the choice of learning methods? What about academic performance? This research paper’s objective is to study the impact of thinking styles on the methods of teaching and academic achievement. There are 186 Albanian university students who participated in the study. The questionnaires were distributed online during the second semester of the 2016-2017 academic year. SPSS 20 and JASP 0.8.1.2 were used for data analysis. The statistical analyses utilized are as follows: distribution table, crossed tabulation, Pearson correlation coefficient, One-Way ANOVA, comparison of means, regression analysis. The study concluded that thinking style has an impact on academic achievement and not on teaching methods. The largest number of students belong to the concrete-sequential category. An additional conclusion is that students who apply different types of thinking rate the hybrid learning as most effective.